2020
DOI: 10.1007/s11095-020-02826-8
|View full text |Cite
|
Sign up to set email alerts
|

L-Type amino acid transporter 1 as a target for drug delivery

Abstract: Our growing understanding of membrane transporters and their substrate specificity has opened a new avenue in the field of targeted drug delivery. The L-type amino acid transporter 1 (LAT1) has been one of the most extensively investigated transporters for delivering drugs across biological barriers. The transporter is predominantly expressed in cerebral cortex, blood-brain barrier, blood-retina barrier, testis, placenta, bone marrow and several types of cancer. Its physiological function is to mediate Na+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 110 publications
5
93
0
Order By: Relevance
“…Notably, a recent study found that LAT1 was a pH-dependent but not pH-independent transporter, whose maximal transporter activity is at neutral pH but much lower at acidic pH (Cosco et al, 2020 ). LAT1 ( SLC7A5 ) imports BCAAs and several essential amino acids (e.g., phenylalanine, leucine, isoleucine, tryptophan, histidine, and tyrosine) with high affinity in exchange for the efflux of intracellular histidine, tyrosine, and glutamine (Nicklin et al, 2009 ; Puris et al, 2020 ). To maintain amino acid nutrition for tumor growth, the expression of the LAT1 ( SLC7A5 ) transporter is controlled by the pro-carcinogenic transcription factors c-Myc (Yue et al, 2017 ), HIF2α (Elorza et al, 2012 ), and NOTCH (Grzes et al, 2017 ), as well as the post-transcriptional regulator miR-126 (Miko et al, 2011 ).…”
Section: Amino Acid Metabolism In Cancermentioning
confidence: 99%
“…Notably, a recent study found that LAT1 was a pH-dependent but not pH-independent transporter, whose maximal transporter activity is at neutral pH but much lower at acidic pH (Cosco et al, 2020 ). LAT1 ( SLC7A5 ) imports BCAAs and several essential amino acids (e.g., phenylalanine, leucine, isoleucine, tryptophan, histidine, and tyrosine) with high affinity in exchange for the efflux of intracellular histidine, tyrosine, and glutamine (Nicklin et al, 2009 ; Puris et al, 2020 ). To maintain amino acid nutrition for tumor growth, the expression of the LAT1 ( SLC7A5 ) transporter is controlled by the pro-carcinogenic transcription factors c-Myc (Yue et al, 2017 ), HIF2α (Elorza et al, 2012 ), and NOTCH (Grzes et al, 2017 ), as well as the post-transcriptional regulator miR-126 (Miko et al, 2011 ).…”
Section: Amino Acid Metabolism In Cancermentioning
confidence: 99%
“…4F2hc-LAT1 is expressed in different tissues and organs (e.g., brain, ovary, placenta and testis), and in relatively high levels at the blood-brain barrier and in several types of tumors (Fotiadis et al, 2013;Scalise et al, 2018;Häfliger and Charles, 2019). The location and high expression levels make 4F2hc-LAT1 an interesting vehicle for drug delivery into the brain and for cancer cell targeting (Häfliger and Charles, 2019;Puris et al, 2020). In cancer cells, 4F2hc-LAT1 provides neutral and essential amino acids for nutrition and regulation of the mTOR signaling pathway (Nicklin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Relative high concentrations in L-leucine result in increased mammalian target of rapamycin (mTOR) activation [ 17 ], which supports growth and survival of cancer cells [ 18 ]. Because of its localization in the blood-brain barrier, 4F2hc-LAT1 is a promising transport system, which is also utilized to shuttle drugs and prodrugs into the brain [ 19 ]. Recently, it was suggested that lack or defects in LAT2 are implicated in age-related hearing loss [ 20 ] and cataract formation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%